A Survey Paper of Study about Phishing and Anti-Phishing Techniques - Patel, Neha; Choudhry, Pooja; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Phishing is a con game that scammers use to collect personal information from unsuspecting users. The false e-mails often look surprisingly legitimate and even the Web pages where users are asked to enter their information may look real. Phishing is similar to fishing in a lake, but instead of trying to capture fish, phishers attempt to steal personal information. This paper gives brief information about phishing, its attacks, steps that users can take to safeguard their confidential information. This paper also shows a survey conducted by netcraft on phishing.